Aplikasi Metode Penetapan Kadar Rutin Parasetamol PT. Kimia Farma, Tbk secara HPLC pada Sediaan Tablet Generik dan Bermerek di Medan - Suprianto Suprianto; Darwin Syamsul; Muhammad Deddy Harfiansyah (Journal of Indah Science and Clinic, 2020)
Paracetamol is a drug that is analgesic and antipyretic, which is produced as a generic or branded drug. The research objective was to determine the quality based on paracetamol levels in generic and branded tablet preparations circulating in Medan. The research used HPLC Alliance e2696 UV / Visible Detector 2489, Column µ Bondapak TMC-18: 10 µm 125A 3.9x300 mm, UV-Vis Spectrophotometer Agilent 8453. The method used was a routine assay method for paracetamol PT. Kimia Farma. The results showed that the paracetamol content in the tablet dosage was 97.05% - 106.04%, according to the Indonesian Pharmacopoeia Edition V, not less than 90% and not more than 110%.